Animals and their moral standing - Clark, Stephen R. L. (Routlege, 1997)
Stephen R. L. Clark is an international authority on animal rights. His major writings over twenty years are now brought together for the first time in one volume as a record of his pioneering work. Over the last decade or more, animal rights has become an issue of genuine and outspoken public concern, following the work of philosophers, scientists and welfarists who have raised awareness of the issue. Renowned for The Moral Status of Animals and The Nature of the Beast, Clark's writings have been central to this debate; this collection traces the development of 'animal rights'. Animals and their Moral Standing tackles issues such as the calculation of costs and benefits; the 'rights' of wild animals, and ecosystems; problems with our understanding of animal behaviour, and the faults of specisism. Written with clarity and insight, these essays are core reading for anyone interested in the debates around animal rights, as well as an invaluable collection for philosophers and scientists.